profile
Опубликовано 1 год назад по предмету Алгебра от rassolov75

(2х-1)(2х+3)(3х-2)(3х+4)=35

  1. Ответ
    Ответ дан Аккаунт удален
    (2х-1)(2х+3)(3х-2)(3х+4)=35

    тогда х=1

  2. Ответ
    Ответ дан mmb1
    (2х-1)(2х+3)(3х-2)(3х+4)=35
    (2х-1)(3x+4)(2х+3)(3х-2)=35
    (6x2+8x-3x-4)(6x2+9x-4x-6)=35
    (6x2+5x-4)(6x2+5x-6)=35
    6x2+5x-4=t
    t(t-2)=35
    t2-2t-35=0
    t=(2+-корень(4+140))/2=2+-12/2= 7 -5
    6x2+5x-4=-5
    6x2+5x+1=0
    x12=корней нет
    6x2+5x-4=7
    6x2+5x-11=0
    x12=(-5+-корень(25+4*6*11))/12=-5+-17 /12= 1  -11/6
    1 b -11/6
Самые новые вопросы